Locally calibrated wave hindcasts in the Estonian coastal sea in 1966–2011 - Ülo Suursaar (Estonian Journal of Earth Sciences, 2013)
Wave parameters were studied in four differently exposed fetch-limited Estonian coastal sea locations: the Harilaid Peninsula facing W–NW, Letipea N–NE, Matsi SW and Kõiguste SE. Based on high-quality measurements of waves with the bottom-mounted Recording Doppler Current Profiler in 2006–2011, a model for significant wave height was calibrated separately for those locations. Using wind forcing data from Estonian coastal meteorological stations, a set of hindcasts was obtained over the period of 1966–2011. The wave heights showed some quasi-periodic cycles with a high stage in 1980–1995, and probably also from 2007; a prevailing overall decrease in the mean wave height; an increase in high wave events at the windward coasts of West Estonia but a decrease at the northern and southeastern coasts. The spatially contrasting results for differently exposed coasts reflect the corresponding variations in local wind, which are probably caused by changes in large-scale atmospheric pressure patterns above Northern Europe and a poleward shift of cyclones’ trajectories. Although featuring outstanding calibration results, the long-term wave hindcast may be impacted by possible inhomogeneities in the older wind data.